2001
DOI: 10.1021/jf010314l
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Methods for Characterization and Classification of Espresso Coffees from Different Botanical Varieties and Types of Roast by Foam, Taste, and Mouthfeel

Abstract: Three espresso coffee (EC) samples of different botanical varieties and types of roast were prepared in standard conditions using an experimental EC prototype: Arabica coffee, Robusta Natural blend, and Robusta Torrefacto blend (a special roast by adding sugar). The ECs were characterized with regard to the physical parameters, amount of total solids, total solids on filtrate, lipids, caffeine, trigonelline, and chlorogenic acids by HPLC, and sensory descriptive analysis related to foam appearance, taste, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 6 publications
4
80
0
2
Order By: Relevance
“…Six aldehydes, 4 ketones and 1 acid were identified and quantified in the headspace of the coffee brews. Methanethiol, a sulphur compound related to aroma freshness in ground roasted coffee (Holscher, & Steinhart, 1992) and espresso coffee (Maeztu et al, 2001a) was found. Nor guaiacol (2-methoxyphenol), responsible for phenolic, spicy and burnt aromas and flavors (Blank et al, 1991;Semmelroch, & Grosch, 1995), was present at detectable levels in the studied coffee brews.…”
Section: Study Of the Influence Of The Uht Treatment On The Coffee Brmentioning
confidence: 96%
See 2 more Smart Citations
“…Six aldehydes, 4 ketones and 1 acid were identified and quantified in the headspace of the coffee brews. Methanethiol, a sulphur compound related to aroma freshness in ground roasted coffee (Holscher, & Steinhart, 1992) and espresso coffee (Maeztu et al, 2001a) was found. Nor guaiacol (2-methoxyphenol), responsible for phenolic, spicy and burnt aromas and flavors (Blank et al, 1991;Semmelroch, & Grosch, 1995), was present at detectable levels in the studied coffee brews.…”
Section: Study Of the Influence Of The Uht Treatment On The Coffee Brmentioning
confidence: 96%
“…Afterwards, the area of 2-propanone and 2-butanone tended to increase until the end of the storage time, reaching values significantly higher than the initial ones. In contrast, 2,3-butanedione and 2,3-pentanedione, key odorants responsible for the buttery flavors in espresso and other coffee brews (Maeztu et al, 2001a;Blank et al, 1991;Semmelroch, & Grosch, 1996), showed a decrease with storage time. This fact could be related to the aroma freshness loss in coffee brews after the the first 8 days of storage.…”
Section: Study Of the Influence Of The Uht Treatment On The Coffee Brmentioning
confidence: 97%
See 1 more Smart Citation
“…The freshly prepared coffee brews were immediately poured into 330 mL sterilized glass flasks, either up to a volume of 135 mL (with air headspace, this is, Caffeine and Trigonelline. Extract preparation, clean-up and HPLC analysis were performed following the method described by Maeztu et al [22]. HPLC analysis was achieved with an analytical HPLC unit (Agilent Technologies 1100), equipped with a binary pump and an automated sample injector.…”
Section: Coffee Brew Preparationmentioning
confidence: 99%
“…1 Most studies on differentiation deals with Arabica and Robusta green and roasted coffees in relation to their major chemical composition such as metal, 2 lipids focused on sterolic and alcohol diterpenes, 3 alkaloids, 4 chlorogenic acids 5 and sugar profiles. 6 Chemometric discrimination using principal component analysis (PCA) has been successfully used as an important tool to differentiate roasting processes, 7 geographical origin of green and roasted coffees 8 and other aspects of coffee process. To search for faster methods for coffee discrimination based on fingerprinting analysis, NIR and NMR studies were also applied.…”
Section: Introductionmentioning
confidence: 99%